2022
DOI: 10.1002/pcn5.7
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for recurrent suicide attempts: Evidence from the ACTION‐J study

Abstract: Aim Risk factors for attempted suicide have been widely studied. However, there is limited evidence on predictive factors for suicide reattempts. We aimed to identify these in suicide attempters admitted to emergency departments. Methods This is the second analysis from a randomized controlled multicenter trial, ACTION‐J. Patient characteristics were extracted from baseline demographic data and clinical data of participants. Predictive factors for a recurrent suicide attempt in each gender were examined using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…13 The secondary analysis also elucidated the importance of visits to a psychiatrist a short time before the first suicide attempt in men and in women with substance-related disorder, previous suicide attempts, and drug overdose in the first suicide attempt as predictive factors for future suicide reattempts. 14 The results of the present study indicated successful implementation of the assertive case management intervention program in a real-world clinical setting. The proportion of suicide attempters in this study who completed the 6-month assertive case management intervention was 72.2%.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…13 The secondary analysis also elucidated the importance of visits to a psychiatrist a short time before the first suicide attempt in men and in women with substance-related disorder, previous suicide attempts, and drug overdose in the first suicide attempt as predictive factors for future suicide reattempts. 14 The results of the present study indicated successful implementation of the assertive case management intervention program in a real-world clinical setting. The proportion of suicide attempters in this study who completed the 6-month assertive case management intervention was 72.2%.…”
Section: Discussionsupporting
confidence: 52%
“…Subsequent secondary analyses of ACTION‐J data also revealed that assertive case management helped prevent suicide reattempts among patients with comorbid DSM‐IV‐TR Axis I and II disorders 11 and those with a history of self‐poisoning, 12 and reduced the overall incidence of self‐harm 13 . The secondary analysis also elucidated the importance of visits to a psychiatrist a short time before the first suicide attempt in men and in women with substance‐related disorder, previous suicide attempts, and drug overdose in the first suicide attempt as predictive factors for future suicide reattempts 14 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation